Spectrum of bone marrow morphologic findings in hepatitis C patients with and without prior liver transplantation. (30th August 2016) - Boone, J. M.; Cui, W.
Summary: Introduction: Cytopenia is a common hematologic finding in patients with HCV infection. Only a few studies have addressed bone marrow (BM) morphologic findings in these patients. No systemic study has been performed in these patients with liver transplantation (LT). Methods: We retrospectively examined BMs in 49 hepatitis C patients with and without prior LT ( n = 19 and n = 30). Results: Among the patients with an available complete blood count ( n = 46), the majority of them presented with cytopenia involving one or multiple cell lineages including unicytopenia (13%, n = 6), bicytopenia (31%, n = 14), and pancytopenia (43%, n = 20). Examination of the BM revealed a wide spectrum of morphologic findings ranging from benign reactive processes to overt malignant processes which included myeloid, lymphoid, and plasma cell neoplasms. The severity of cytopenia was not correlated with cirrhosis or antiviral therapy. However, the severity of cytopenia was partly correlated with splenomegaly or LT ( P < 0.05). Conclusions: Cytopenia is a common finding in hepatitis C patients. Hypersplenism or LT has an adverse impact on some blood cell counts. Lastly, hepatitis C patients present with a wide spectrum of BM findings including malignant neoplasms, which indicates a diagnostic value of BM examination in these patients.